Experimental investigations on the kinetics of void shrinkage in solid state bonding of AA6061 at high temperatures and high pressures. (5th January 2016) - Chen, Gaoqiang; Shi, Qingyu; Li, Yujia; Han, Zandong; Yuan, Keyi
Abstract: Physical simulation experiments by Gleeble are utilized to understand the kinetics of void shrinkage in solid state bonding at high temperatures and high pressures. By quantifying the void volume via ultrasonic echo magnitude at the bonding interfaces, a mathematical model is established to link the percentage of void shrinkage to the processing conditions. A new equation is proposed to predict the required time for complete void closure, which provides a practical guide line to design the processing conditions for solid state bonding. Graphical abstract: Highlights: The void shrinkage is quantified by ultrasonic echo magnitude at the interfaces. A mathematical model for the kinetics of void shrinkage is established. A new equation is proposed to predict the required time for void closure.